Molecular Conductance through a Quadruple‐Hydrogen‐Bond‐Bridged Supramolecular Junction. (31st August 2016) - Wang, Lin; Gong, Zhong‐Liang; Li, Shu‐Ying; Hong, Wenjing; Zhong, Yu‐Wu; Wang, Dong; Wan, Li‐Jun
Abstract: A series of self‐complementary ureido pyrimidinedione (UPy) derivatives modified with different aurophilic anchoring groups were synthesized. Their electron transport properties through the quadruple hydrogen bonds in apolar solvent were probed employing the scanning tunneling microscopy break junction (STMBJ) technique. The molecule terminated with a thiol shows the optimal electron transport properties, with a statistical conductance value that approaches 10 −3 G0 . The 1 H NMR spectra and control experiments verify the formation of quadruple hydrogen bonds, which can be effectively modulated by the polarity of the solvent environment. These findings provide a new design strategy for supramolecular circuit elements in molecular electronics.